Landasan Pengembangan Kurikulum Pendidikan Islam - Riyadi, Sugeng; Firdaus, Ahmad Sofwan; Yennizar.N, Yennizar.N; Latif, Mukhtar (RIGGS: Journal of Artificial Intelligence and Digital Business, 2025)
This study aims to comprehensively examine the various foundations underlying the development of the Islamic education curriculum. In Islamic education, the curriculum functions not only as a learning guide but also as a medium for holistically transmitting Islamic values. Amid the challenges of globalization, technological advancements, and socio-cultural changes, the Islamic education curriculum is required to remain relevant without neglecting the fundamental principles of Islamic teachings. Therefore, a deep understanding of theological, philosophical, psychological, sociological, cultural, and scientific-technology foundations is essential. This study employs a descriptive qualitative approach through literature analysis to explore the interrelationships among these foundations. The findings indicate that an integrative approach to curriculum development can produce Muslim generations who are not only knowledgeable but also possess Islamic character and adaptability to contemporary changes. Thus, the curriculum serves as a strategic instrument in realizing the holistic objectives of Islamic education.